Fundamental Limit on ``Interaction Free'' Measurements - Simon, S; Platzman, P (1999)
In ``interaction free'' measurements, one typically wants to detect the presence of an object without touching it with even a single photon. One often imagines a bomb whose trigger is an extremely sensitive measuring device whose presence we would like to detect without triggering it. We point out that all such measuring devices have a maximum sensitivity set by the uncertainty principle, and thus can only determine whether a measurement is ``interaction free'' to within a finite minimum resolution. We further discuss exactly what can be achieved with the proposed ``interaction free'' measurement schemes.